1980
DOI: 10.1177/009524438001200405
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultraviolet Irradiation On Polyurethane Solution and On Solid Polymer

Abstract: The course of photodegradation of polyurethane based on tolylene diisocyanate and polyoxypropylene glycol has been studied. The influence of the physical state of the polymer and of the irradiation dose on the reactions was establ ished.The action of light and oxygen leads to the breaking of N-C and C-O bonds in the urethane group of the polymer, and to formation of aromatic amino, azo and carbonyl containing structures, via hydroperoxides. The oxidation of polymer is associated with the progressive darkening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…The mechanism for photolysis of polyurethane has been discussed, [1][2][3] and the reaction is believed to occur by either (a) rearrangement by the photo-Fries model or (b) formation of quinone compounds. Scheme 3 shows an analogous photoFries mechanism for the model bisphenol biscarbamates that results in the formation of aniline, para-photo-Fries, and ortho-photo-Fries products.…”
Section: Photolysis Of Model Compounds In Dmfmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism for photolysis of polyurethane has been discussed, [1][2][3] and the reaction is believed to occur by either (a) rearrangement by the photo-Fries model or (b) formation of quinone compounds. Scheme 3 shows an analogous photoFries mechanism for the model bisphenol biscarbamates that results in the formation of aniline, para-photo-Fries, and ortho-photo-Fries products.…”
Section: Photolysis Of Model Compounds In Dmfmentioning
confidence: 99%
“…As a result, the photodecomposition of aromatic diisocyanatebased polyurethanes has been investigated by several researchers over the past three decades. [1][2][3][4][5][6][7] However, the exact mechanism of photodecomposition is obscure. Using an analogy based on studies of aryl monocarbamate compounds such as ethyl N-phenylcarbamate, 8 -11 it has been implied that MDI-based polyurethanes photodecompose, at least to some extent, by a photo-Fries rearrangement process (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, of course, severely limits their use in situations which require even moderate exposure to sunlight. As a consequence, considerable attention has been given over the past two decades to the study of the photodegradation process of aromatic diisocyanate based polyurethanes (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study we reported the effect of UV irradiation on PUR based on tolylene diisocyanate and polyoxypropylene glycol (12).…”
Section: Introduction He Oxidative Degradation Of Polyurethane Pur mentioning
confidence: 99%